Beyond schooling: Push and pull strategies to integrate immigrants in the community - Naiditch, Fernando (Frontiers in Education, 2022)
More than one million immigrants arrive in the United States each year. The diversity of languages and cultures brought by immigrants makes America a more multicultural and inclusive nation, but also presents some challenges as immigrants engage in their socialization process. Schools play a central role in acculturating immigrant families and their children, and they serve as mediators of the relationships between these families and the larger society. This article describes a project in a school district in New Jersey that focuses on integrating immigrant families in the community. The framework we developed includes a number of strategies that were grouped into two categories: “push” and “pull.” Push strategies refer to the strategies developed by the school to offer families resources and connect them to an array of services that assist immigrants. Pull strategies focus on bringing families from the community to the school building and creating mechanisms to include them in both curricular and extra-curricular activities to strengthen their sense of belonging and identity.